Real-world treatment patterns of gout patients treated with colchicine or other common treatments for gout in acute care settings: a retrospective chart review study. (3rd August 2015) - Shiozawa, Aki; Cloutier, Martin; Heroux, Julie; Guerin, Annie; Wu, Eric Q.; Jackson, Robert
Abstract: Objective: To describe real-world treatment patterns of patients receiving colchicine or other treatments during a gout-related emergency room or acute care facility (ER/ACF) visit. Methods: An online physician-administered questionnaire was used to collect chart data on 500 patients with a gout-related ER/ACF visit after 16 October 2009; 250 patients receiving colchicine (Colchicine Cohort) and 250 receiving NSAIDs, systemic corticosteroids, narcotics, allopurinol, febuxostat, pegloticase, probenecid, or sulfinpyrazone (Other Cohort). Patient characteristics and treatment received/prescribed during the ER/ACF visit (Period 1 [P1]), at discharge (P2), and at the first follow-up visit (P3) are reported. Results: A total of 45 rheumatologists and 63 primary care physicians participated in the study. Patient mean age was 51 years and 74.8% were male. The most common treatments in the Other Cohort were NSAIDs (59.6%), systemic corticosteroids (45.2%), and narcotics (33.6%). The 500 patients contributed 307 distinct treatment patterns from P1 to P3. Of the 20.6% patients not prescribed a treatment in P2, 60.2% were restarted on a treatment in P3. Of the 78.6% treated patients in P2, 27.0% had a treatment adjustment (dose increase, treatment add-on, or initiation of a different gout-related treatment – not with a urate lowering therapy only) in P3; for 72.6% of these patients, physicians justified the treatment adjustment by inadequacy of the treatment for maintenance therapy, insufficient dosage, or inadequate response. In the Colchicine Cohort, 60.8% of patients were prescribed colchicine consistently from P1 to P3, while 26.8% and 17.7% of patients in the Other Cohort were prescribed consistently NSAIDs and systemic corticosteroids from P1 to P3, respectively. Limitations: Specific nature of the acute gout-related symptoms or potential attack/flare during the ER/ACF visit was not recorded. Conclusion: Real-world clinical practice reveals a substantial number of distinct treatment patterns and frequent treatment adjustments by treating physicians for patients with a gout-related ER/ACF visit.